Generation of attosecond pulse pair in polar media by chirped few-cycle pulses. (24th August 2016) - Hu, Pidong; Niu, Yueping; Wang, Xiangxin; Gong, Shangqing; Liu, Chengpu
Abstract: The high-order harmonic generation in a polar medium driven by an initially chirped few-cycle laser pulse is investigated via numerically solving the nonlinear Bloch or Maxwell-Bloch equations based on whether propagation effects are taken into account or not. As a result of the reduction of quantum trajectories number due to the introduction of chirps, an attosecond pulse pair (APP) is generated instead of a general attosecond pulse train. Moreover, the time delay between the two attosecond pulses is tunable. When propagation effects take roles, the peak intensities of the APP can be enhanced at suitable propagation distances without observable duration broadening, and such an enhancement can be modulated by changing medium density.